Integrated management of childhood illness training needs on cadre for improve family and community capacity in simple handling of respiratory infection, diarrhoea, and less nutrition in children - Solikhah, Umi; Kusnanto, Hari; Haryanti, Fitri; Prabandari, Yayi Suryo (International Journal of Research in Medical Sciences, 2017)
Background: Public awareness towards health services access required involvement of active community participation in health care neonatal, infant, and toddler through the efforts of Integrated Management of Childhood Illness (IMCI) at community. Cases of respiratory infections, diarrhoea and malnutrition is still a problem which needs to be resolved. The purpose to describe children health of the implementation of IMCI results and the possibility of involving the community through the ability of cadres in the management of sick children. Methods: The method used is descriptive study, to describe the health of children and overview of the community needs through involvement of cadre in the success of IMCI. Data from the documentation Banyumas district health offices, health workers, and cadres. The sample size of cadre are 605. Results: Results of the analysis showed that 54% of health centers has not been achieved coverage mortality rate of infants and toddlers. 5 of 10 cases patient who visit came after five days of fever, diarrhoea as endemic case (46.5%), pneumonia (21.4%), malnutrition (7.82%). Active cadre resource support for involvement in the community. Cadre weighing activities every month. IMCI coverage as low as 37%. It takes training a cadre of IMCI in the community as a step involving the community in the achievement of optimal health care, particularly focused on community issues. Furthermore, cadre as a companion of families and communities to resolve the health problems of children. Conclusions: IMCI training to cadre priority to improve the ability of families and communities in simple handling for respiratory infection, diarrhoea, and malnutrition.